An Analysis of Speaking Learning Strategies Used by Proficient Learners of English Language and Literature Department in Universitas Negeri Padang - Dewi Patmawati; Zul Amri; Sitti Fatimah (Journal of English Language Teaching, 2018)
This research is a qualitative descriptive research that aims to see the level of strategy used by smart students who get the value A. data collection techniques used in this study is a questionnaire and focus group discussion of students majoring in English year entered 2016/2017. Based on the research, it was found that dominant students use affective strategies with an average of 4.8 high levels. Metacognitive strategies also get high level results with an average of 4.6. Here are the medium levels on the cognitive strategy with an average of 2.9, the social strategy with an average of 2.8, the compensation strategy with an average of 2.74 and the strategy memory with an average of 2.70. So it can be concluded that affective strategy is the dominant strategy used by smart students who score A in English majors.Keywords: Speaking, Language learning strategy, Student is smart